On Theory and Practice. Issue 1 (July 2017) - Derrida, Jacques
Abstract : This excerpt drawn from Derrida's 1976–77 seminar series of the same title traces surprising resonances between Althusser's and Heidegger's readings of Marx, drawing what Heidegger calls 'thinking' into proximity with what Althusser calls 'praxis'.